Mandibulectomy in Desmoblastic Ameloblastoma: Physiotherapeutic Approach in a Sporadic Oral Surgery Case - Deepali Patil1 , Waqar M. Naqvi2 , Pratik Phansopkar3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Ameloblastomas are slow-growing lesion with local infiltrative and odontogenic tumors ofepithelial origin. Desmoblastic ameloblastoma is traditionally considered to be a subtype of SMA.The purpose of this case report is to describe the physiotherapy rehabilitation in mandibulectomy of the rightside. A patient chief complaint was inability to open mouth, inability to eat food, impaired cognitive and socialbehavior. The primary goals of mandibular reconstruction are feature restoration and an appropriate cosmeticoutcome. The diagnosis of desmoblastic ameloblastoma was confirmed by bone biopsy. Mandibulectomy ofright side done due to desmoblastic ameloblastoma. Physiotherapy treatment is found to be best to resolvepatient’s chief complaints.Results: The case report demonstrated that patients with Mandibulectomy with minimal mouth openingregain near-normal range and improvement in social skills.Conclusion: The patient was able to do essential activities of daily living like eating and talking withoutpain and regain near-normal face appearance due to physiotherapy intervention.